Efforts to Improve Immunization Coverage during Pregnancy among Ob-Gyns. (26th January 2016) - Jones, Katherine M.; Carroll, Sarah; Hawks, Debra; McElwain, Cora-Ann; Schulkin, Jay
Abstract : Background. Influenza and Tdap vaccines are vital factors for improving maternal and neonatal health outcomes. Methods. A prospective, longitudinal study was conducted to determine whether the American College of Obstetricians and Gynecologists' (ACOG's) efforts to increase ob-gyn use of their immunization toolkits and vaccination administration were successful. Pre- and postintervention questionnaires were mailed to a random sample of 1, 500 ACOG members between August 2012 and July 2015. Results. Significantly more postintervention survey ob-gyns reported that they received the immunization toolkits than preintervention survey ob-gyns (84.5% versus 67.0%, p < . 001 ). The large majority of ob-gyns from both surveys (76.9% versus 78.9%) reported that they offered or planned to offer influenza vaccinations to their patients for the 2012-2013 and 2014-2015 flu seasons. Postintervention survey respondents were significantly more likely than preintervention survey participants to report that they routinely offer Tdap vaccinations to all patients during pregnancy (76.8% versus 59.3%, p < . 001 ). Conclusion. ACOG's efforts to improve ob-gyn use of immunization toolkits and vaccine administration appear to have been successful in several ways. ACOG's toolkits are an example of an effective intervention to overcome barriers to offering vaccines and help improve influenza and Tdap immunization coverage for pregnant women.